IMPLEMENTATION OF THE E-ARCHIVE SYSTEM TO INCREASE TRANSPARENCY AND ACCOUNTABILITY OF VILLAGE ARCHIVE MANAGEMENT - Saputra, Ricco Herdiyan; Waziana, Winia; Putra, Aditya Dwi (Asia Information System Journal, 2025)
The development of information technology has encouraged digitalization in various aspects of government, including archive management. This study aims to analyze the implementation of the E-Archive System in Kalirejo Village, Central Lampung, as well as its impact on transparency and accountability in village archive management. The research method used is quantitative descriptive with data collection techniques through observation, interviews, and questionnaires given to administrative staff and users of the E-Archive system. The results of the study show that implementing the E-Archive System has increased efficiency in the search and management of archives, reduced the risk of document loss, and accelerated the administrative process. In addition, the system also strengthens transparency by allowing stakeholders to access more structured and easy-to-trace data. In terms of accountability, E-Archives helps in maintaining the accuracy and security of documents, thereby reducing the potential for errors in the storage and management of records. The implementation of this system also contributes to increasing user satisfaction, lowering operational costs, and improving the village archive supervision and audit system. Although there are still some challenges in the adoption of this system, such as limited technological infrastructure and training needs for village staff, overall, E-Archives has proven to be an effective solution in modernizing archive management at the village level. Thus, this study provides recommendations for strengthening technological infrastructure, increasing human resource capacity, and optimizing system features to ensure the sustainability and effectiveness of E-Archives in supporting more transparent and accountable village governance.